Emotions, technology, and design - Tettegah, Sahron Y.; Noble, Safiya Umoja (Amsterdam Elesevier, Incorporated, 2016)
"Emotions, Technology, and Design addresses the emotional relationship between the objects and the subjects of design--objects being technologies, and subjects being technology users. Using philosophy and theory of emotional design as a foundation, the book discusses emotional design principles, the design and use of emoticons, and intelligent agents in a variety of settings. The volume thoroughly examines how technology design affects emotions and how to use that understanding in practical applications, and explores future research and directions."--Page 4 of cover.
Section I. Experiments and theories in emotions, technology, and design. Emotional screen : color and moving images in digital media / Federico Pierotti -- Safe and sound : using audio to communicate comfort, safety, and familiarity in digital media / Michael L. Austin -- Emoticons in business communication : is the :) worth it? / Jennifer M. Loglia, Clint A. Bowers -- Empathetic technology / Néna Roa Seïler, Paul Craig -- Spoken dialog agent applications using emotional expressions / Kaoru Sumi -- Engaging learners through rational design of multisensory effects / Debbie Denise Reese, Dianne R.V. Pawluk, Curtis R. Taylor -- Designing interaction strategies for companions interacting with children / Néna Roa Seïler -- Section II. Critical theoretical engagements with emotions, technology, and design. The emulation of emotions in artificial intelligence : another step into anthropomorphism / Mariana Goya-Martinez -- Through Google-colored glass(es) : design, emotion, class, and wearables as commodity and control / Safiya Umoja Noble, Sarah T. Roberts -- Designing emotions : Deliver the nets, eradicate malaria in Africa, and feel good? / Ergin Bulut, Robert Mejia -- Police body cameras : emotional mediation and the economies of visuality / Stacy Wood.
Includes bibliographical references and index.
Keywords: Human-computer interaction; Technology -- Social aspects; Technology -- Psychological aspects; Educational innovations; Emotions